2016
DOI: 10.3389/fpsyg.2016.00192
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Functional Neuroimaging and Cognitive Control Studies in Schizophrenia: Preliminary Elucidation of a Core Dysfunctional Timing Network

Abstract: Timing and other cognitive processes demanding cognitive control become interlinked when there is an increase in the level of difficulty or effort required. Both functions are interrelated and share neuroanatomical bases. A previous meta-analysis of neuroimaging studies found that people with schizophrenia had significantly lower activation, relative to normal controls, of most right hemisphere regions of the time circuit. This finding suggests that a pattern of disconnectivity of this circuit, particularly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 90 publications
2
17
0
17
Order By: Relevance
“…It is also interesting to note that the time overestimation pattern reported in our research for the PTSD sample appears similar to data in schizophrenic patients (ref. 52 , for a review 53 ). This parallelism is not surprising as the links between childhood trauma, PTSD and psychotic disorders is increasingly recognized 54 , and because in a discrete number of patients these two conditions might even overlap (see ref.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that the time overestimation pattern reported in our research for the PTSD sample appears similar to data in schizophrenic patients (ref. 52 , for a review 53 ). This parallelism is not surprising as the links between childhood trauma, PTSD and psychotic disorders is increasingly recognized 54 , and because in a discrete number of patients these two conditions might even overlap (see ref.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, temporal variability in the production task increased linearly with both duration of illness and age of SZ patients thus suggesting that dysfunctions in a fronto-thalamo-striatal control network ( Andreasen et al, 1998 ; Banaj et al, 2018 ), presumably hypo-activated ( Alústiza et al, 2016 ) or disorganized already at early stages of the illness ( Alústiza et al, 2016 ; Lambe et al, 2006 ), might mediate the observed variability, as it is involved in both time processing and the cognitive resources required for timing tasks ( Radua et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Voss et al (2017) identified the angular gyrus and DLPFC as being implicated in matching outcomes to actions and observed decreased connectivity between these regions in SZ. As hypoactivation of the inferior parietal gyri has been observed in SZ patients in TP (Alustiza et al, 2016), future studies should employ binding paradigms (e.g., Haggard et al, 2003) to examine neural activation during TP in SZ. Interestingly, Lošák et al (2016) found decreased activation of the cerebellar vermis in SZ patients correlated with a faster clock during a time prediction task, suggesting that this region is critical for time prediction during salient events.…”
Section: Implications For Schizophreniamentioning
confidence: 99%